Scenarios for future sourcing strategies Iin Tthe context of the use of green hydrogen to achieve carbon neutrality in dortmund by 2035 - strategic implications for dew21 - phase Ii: explore - megatrend I & Megatrend Ii - Grabowski, Philip (2022)
: In the subsequent individual work, “Phase: II – Explore” of the applied intuitive logics school scenario building framework is conducted. In this phase, DEW21’s contextual business environment is analysed with special regard to green hydrogen developments on a regional, national, European and global level. Influential drivers of change, such as megatrends and trends are displayed to capture essential and impactful green hydrogen developments, and by this, opening the space for tangible business recommendation for DEW21 in a later stage of the work project.